Altered representation of expected value in the orbitofrontal cortex in mania - Bermpohl, Felix (Hum Brain Mapp, 2009)
Objective: Increased responsiveness to appetitive and reduced responsiveness to aversive anticipatory cues may be associated with dysfunction of the brain reward system in mania. Here we studied neural correlates of gain and loss expectation in mania using functional magnetic resonance imaging (fMRI). Method: Fifteen manic patients and 26 matched healthy control individuals performed a monetary incentive delay task, during which subjects anticipated to win or lose a varying amount of money. Varying both magnitude and valence (win, loss) of anticipatory cues allowed us to isolate the effects of magnitude, valence and expected value (magnitude‐by‐valence interaction). Results: Response times and total gain amount did not differ significantly between groups. FMRI data indicated that the ventral striatum responded according to cued incentive magnitude in both groups, and this effect did not significantly differ between groups. However, a significant group difference was observed for expected value representation in the left lateral orbitofrontal cortex (OFC; BA 11 and 47). In this region, patients showed increasing BOLD responses during expectation of increasing gain and decreasing responses during expectation of increasing loss, while healthy subjects tended to show the inverse effect. In seven patients retested after remission OFC responses adapted to the response pattern of healthy controls. Conclusions: The observed alterations are consistent with a state‐related affective processing bias during the expectation of gains and losses which may contribute to clinical features of mania, such as the enhanced motivation for seeking rewards and the underestimation of risks and potential punishments. Hum Brain Mapp, 2010. © 2009 Wiley‐Liss, Inc.